2023
DOI: 10.3390/sports11040074
|View full text |Cite
|
Sign up to set email alerts
|

The Acute and Chronic Effects of Resistance and Aerobic Exercise in Hemostatic Balance: A Brief Review

Abstract: Hemostatic balance refers to the dynamic balance between blood clot formation (coagulation), blood clot dissolution (fibrinolysis), anticoagulation, and innate immunity. Although regular habitual exercise may lower the incidence of cardiovascular diseases (CVD) by improving an individual’s hemostatic profile at rest and during exertion, vigorous exercise may increase the risk of sudden cardiac death and venous thromboembolism (VTE). This literature review aims to investigate the hemostatic system’s acute and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 242 publications
1
13
0
Order By: Relevance
“…Nonetheless, intensity can be the rate-limiting factor for physical activity–mediated positive effects. Some studies report that high-intensity physical activity (<75% VO 2 max) led to CTC–platelet aggregation ( Wang et al, 2022 ; Skouras et al, 2023 ), while moderate physical activity (50%–74% VO 2 max) prevented both adhesiveness and aggregation of platelets ( Barale et al, 2023 ).…”
Section: Immunitymentioning
confidence: 99%
“…Nonetheless, intensity can be the rate-limiting factor for physical activity–mediated positive effects. Some studies report that high-intensity physical activity (<75% VO 2 max) led to CTC–platelet aggregation ( Wang et al, 2022 ; Skouras et al, 2023 ), while moderate physical activity (50%–74% VO 2 max) prevented both adhesiveness and aggregation of platelets ( Barale et al, 2023 ).…”
Section: Immunitymentioning
confidence: 99%
“…Considering this, acute exercise without chronic adaptation may paradoxically interfere with platelet responsiveness in a detrimental way through reduced NO bioavailability and ox-LDL generation [ 75 ]. Nevertheless, the exact effect of an acute bout of exercise on platelet function is still unclear [ 86 , 87 ].…”
Section: Exercise Effects On Platelet Responsivenessmentioning
confidence: 99%
“…The mechanisms underlying these different effects on thrombotic processes involve platelets, fibrinolytic, and coagulation activity. Specifically, acute but light exercise (under 49% VO 2 max) increases fibrinolytic activity but does not interfere with platelet reactivity and coagulation, while if moderate, acute exercise (50–74% VO 2 max) inhibits platelet reactivity and enhances fibrinolysis without modifying the coagulation system; whereas if vigorous, acute exercise (more than 75% VO 2 max) activates both platelets and the coagulation system, besides promoting fibrinolytic activity [ 87 , 133 ]. Thus, on the one side, the adaptation to moderate-intensity exercise attenuates platelet reactivity and increases fibrinolysis at rest; on the other side, during strenuous exercise, it limits enhanced platelet reactivity and sustains hyper-fibrinolytic activity.…”
Section: Platelets In Exercise Adaptation and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed the biomechanical changes that occur in smokers with a significant abnormality in the HR response [37]. In smokers during exercise, signals from the cardiac parasympathetic blockade cause the stimulation of mechanoreceptors to inhibit the stimulation of the activation of parasympathetic activity resulting in a drastic inverse outcome of its effects [27,35].…”
Section: Exercise and Cardiovascular Functionmentioning
confidence: 99%